International Committee of Red Cross versus International Red Crescent: The Recent Practices as Subject International Law - Arifin, Ridwan; Zulfa, Zaeda; Saraswati, Dhann (International Law Discourse in Southeast Asia, 2022)
The International Red Cross has different characteristics so that in its development, this organization is accepted as one of the subjects of international law. However, the International Red Cross has limitations in the subject of law. International treaties such as the 1949 Red Cross Conventions provide certain rights and obligations. The rights and obligations are given by the convention indirectly to individuals through the country that is a participant in the convention. Through such construction, many individual circumstances or events that are subject to international law based on a convention can be returned to the countries that are participants in such a convention, namely the Convention on the Settlement of Investment Disputes between States and Nationals of Other States and The European Convention on Human Rights. This study analyzes recent developments regarding the International Red Cross as a subject of international law. This study also analyzes the position of the International Red Crescent as one of the subjects of international law in practice.